Is the Covid-19 Pandemic Rewriting the Rules of Corporate Governance in Nigeria? - Oyesola Animashaun; Howard Chitimira (Perspectives of Law and Public Administration, 2022)
The corona virus (covid-19) pandemic which started as a public health emergency swiftly evolved into a global financial and economic crisis of epic proportions. Thus, it had a far-reaching effect on Nigerian corporations. The advent of covid-19 seems to have changed the guiding principles of corporate governance from the agency theory to stakeholder theory due to the heightened expectations for societal engagement from corporations in Nigeria. For instance, the management of Access Bank which donated 1 Billion and other materials like ambulances to the Federal Government of Nigeria, decided to downsize staff by 75 percent in the same week. The outcry by the public on the challenges caused by the aforesaid huge donation vis-à-vis the redundancy policy led Access Bank’s management to reverse its earlier decision and for the regulatory body for the banking industry, the Central Bank of Nigeria, to prohibit all banks in Nigeria from retrenching their employees during the pendency of the pandemic. The article examines the impact of covid-19 on corporate governance in Nigeria through the prism of stakeholder theories of corporate governance. The authors submit that covid-19 has a profound effect on corporate governance in Nigeria and it seems to be inducing a review and amendment of certain provisions of Companies and Allied Matters Act, 2020 to promote good corporate governance in Nigeria.